Pengembangan Media Pembelajaran Computerised Pictograph (Compic) Berbantuan Papan Pintar pada Materi Benda Hidup dan Benda Tak Hidup Untuk Siswa Kelas 1 SD - Eny ndriastuti; Farizal Imansyah; Imelda Ratih Ayu (Departement of Mathematics Education, 2024)
This study aimed to produce the learning products in the form of computerised pictograph (compic) media that assisted by smart boards that are valid and practical on Living and Non-Living Objects Around Us for grade I students in SD Negeri 95 Palembang. This research is a research and development (R&D) that use the Borg and Gall development model that is modified by researcher adjusted to research need. This research instrument use a questionnaire. The small-scale test subject in this study consisted of 5 student while the large-scale test were 20 students who then produced smart board-assisted compic media. The result of the validation of the instructional media experts obtained an average score of 87,5% with the category “Very Eligible”. The result of the validation of learning material experts obtained an average score of 100% with the category “Very Eligible”. The result of the validation of Indonesian language experts obtained an average score of 95% with the category “Very Eligible”. While the results of small-scale trials obtained an average score of 90% with the category of “Very Good” and the results of large-scale trials obtained an average score of 90,5% with the category of “Very Good”. The results of the expert team’s validation and small-scale trials as well as large-scale trial showed that computerized pictograph (compic) media with smart board-assisted on Living and Non-Living Objects Around Us were included in valid and practical category used as a learning media